Safety and Biocompatibility of Aflibercept-Loaded Microsphere Thermo-Responsive Hydrogel Drug Delivery System in a Nonhuman Primate Model - Kim, Soohyun (Transl Vis Sci Technol, 2020)
PURPOSE: To evaluate the safety and tolerability of a microsphere thermo-responsive hydrogel drug delivery system (DDS) loaded with aflibercept in a nonhuman primate model. METHODS: A sterile 50 µL of aflibercept-loaded microsphere thermo-responsive hydrogel-DDS (aflibercept-DDS) was injected intravitreally into the right eye of 10 healthy rhesus macaques. A complete ophthalmic examination, intraocular pressure (IOP) measurement, fundus photography, spectral-domain optical coherence tomography (SD-OCT), and electroretinogram were performed monthly for 6 months. One macaque was euthanized monthly, and the enucleated eyes were submitted for measurement of bioactive aflibercept concentrations. Four eyes were submitted for histopathology. RESULTS: Injected aflibercept-DDS was visualized in the vitreous until 6 months postinjection. No abnormalities were observed in the anterior segment, and IOP remained within normal range during the study period. A small number of cells were observed in the vitreous of some macaques, but otherwise the remainder of the posterior segment examination was normal. No significant changes in retinal architecture or function as assessed by SD-OCT and histology or full-field electroretinography, respectively, were observed. A mild, focal foreign body reaction around the injectate was observed with histology at 6 months postinjection. A mean of 2.1 ng/µL of aflibercept was measured in the vitreous. CONCLUSIONS: Intravitreally injected aflibercept-DDS achieved controlled, sustained release of aflibercept with no adverse effects for up to 6 months in the eyes of healthy rhesus macaques. TRANSLATIONAL RELEVANCE: Aflibercept-DDS may be a more effective method to deliver bioactive antivascular endothelial growth factor agents than current practice by reducing the frequency of intravitreal injections and providing controlled drug release.